The long term impact of french settlement on education in Algeria - Ouarda Merrouche (Centre for Microdata Methods and Practice (cemmap), 2006)
In settlement colonies, the economic systems, infrastructure and development projects of the settlers exclusively served their own needs. The disastrous outcomes of this discrimination became apparent in the post-colonial era particularly as regards education. In Algeria under French rule (1930-1962) education was almost exclusively reserved to French and other European settlers and as a consequence only ten per cent of Muslim Algerians were literate at independence. While the majority of the settlers left Algeria in 1962, the infrastructure remained. This paper exploits substantial regional variations in the non-Muslims proportion of the population on the eve of the war of independence (1954) in Algeria to evaluate the long term impact of colonial discrimination in public goods allocation on education levels. Using an instrumental variables approach to correct for endogeneous sorting of settlers and natives into regions my results indicate that settlement regions, which inherited a larger stock of infrastructure per capita at independence, have persistently higher literacy rates relative to extractive regions. However, these disparities tend to vanish over time probably as a result of the massive funds allocated to the education sector by the successive governments in the post-independence era.
Keywords: 330; Kolonialismus; Einwanderung; Franzosen; Bildungsinvestition; Bildungsniveau; Algerien